Legal grounds and procedure for obtaining information by public bodies: comparative approach - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article an author analyze different ways of legal regulation about getting of information with the foreign experience. An author in the example of foreign countries takes into account features of such ways. Also, in the article describes the features of European politics in a sphere of informative relations.